2023
DOI: 10.26508/lsa.202201730
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of SERF2 in mice delays embryonic development and alters amyloid deposit structure in the brain

Abstract: In age-related neurodegenerative diseases, like Alzheimer’s and Parkinson’s, disease-specific proteins become aggregation-prone and form amyloid-like deposits. Depletion of SERF proteins ameliorates this toxic process in worm and human cell models for diseases. Whether SERF modifies amyloid pathology in mammalian brain, however, has remained unknown. Here, we generated conditionalSerf2knockout mice and found that full-body deletion ofSerf2delayed embryonic development, causing premature birth and perinatal let… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 86 publications
(122 reference statements)
0
2
0
Order By: Relevance
“…Importantly, distinguished from the conventional mechanisms, SERF decreases the α-Syn aggregation toxicity through attenuating the accumulation of the more toxic α-Syn oligomer species, which might serve as a novel mechanism of intracellular self-protection. A recent study ( 44 ) suggested that the brain depletion of SERF2 altered the structure of amyloid-β deposits. However, there was no compensatory upregulation of SERF1 in response to SERF2 knockout, which provides a direction for our forthcoming work.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, distinguished from the conventional mechanisms, SERF decreases the α-Syn aggregation toxicity through attenuating the accumulation of the more toxic α-Syn oligomer species, which might serve as a novel mechanism of intracellular self-protection. A recent study ( 44 ) suggested that the brain depletion of SERF2 altered the structure of amyloid-β deposits. However, there was no compensatory upregulation of SERF1 in response to SERF2 knockout, which provides a direction for our forthcoming work.…”
Section: Discussionmentioning
confidence: 99%
“…SERF2 has been shown in a peptide microarray analysis to bind many amyloidogenic peptide sequences (Pras et al 2021). SERF2 function has also been shown to be linked with developmental de cits and embryonic lethality (Cleverley et al 2021;Stroo et al 2023). While the pathological role of SERF2 is reasonably well established, its physiological function(s) remain poorly explored, though it has recently been shown to bind nucleic acids, particularly G4 quadruplex forming sequences (Sahoo et al 2023).…”
mentioning
confidence: 99%